Reconstitution of DNA strand exchange mediated by Rhp51 recombinase and two mediators. - Yumiko Kurokawa (Public Library of Science (PLoS), 2008)
In the fission yeast Schizosaccharomyces pombe, genetic evidence suggests that two mediators, Rad22 (the S. pombe Rad52 homolog) and the Swi5-Sfr1 complex, participate in a common pathway of Rhp51 (the S. pombe Rad51 homolog)-mediated homologous recombination (HR) and HR repair. Here, we have demonstrated an in vitro reconstitution of the central step of DNA strand exchange during HR. Our system consists entirely of homogeneously purified proteins, including Rhp51, the two mediators, and replication protein A (RPA), which reflects genetic requirements in vivo. Using this system, we present the first robust biochemical evidence that concerted action of the two mediators directs the loading of Rhp51 onto single-stranded DNA (ssDNA) precoated with RPA. Dissection of the reaction reveals that Rad22 overcomes the inhibitory effect of RPA on Rhp51-Swi5-Sfr1-mediated strand exchange. In addition, Rad22 negates the requirement for a strict order of protein addition to the in vitro system. However, despite the presence of Rad22, Swi5-Sfr1 is still essential for strand exchange. Importantly, Rhp51, but neither Rad22 nor the Swi5-Sfr1 mediator, is the factor that displaces RPA from ssDNA. Swi5-Sfr1 stabilizes Rhp51-ssDNA filaments in an ATP-dependent manner, and this stabilization is correlated with activation of Rhp51 for the strand exchange reaction. Rad22 alone cannot activate the Rhp51 presynaptic filament. AMP-PNP, a nonhydrolyzable ATP analog, induces a similar stabilization of Rhp51, but this stabilization is independent of Swi5-Sfr1. However, hydrolysis of ATP is required for processive strand transfer, which results in the formation of a long heteroduplex. Our in vitro reconstitution system has revealed that the two mediators have indispensable, but distinct, roles for mediating Rhp51 loading onto RPA-precoated ssDNA.